Economic Efficiency of Photovoltaic Installations (A Case Study at the Zwierzyniec–Biały Słup Research and Education Centre of Roztocze National Park) - Piotr Gradziuk (Barometr Regionalny)
The paper presents an assessment of the economic efficiency of a 21 kW photovoltaic system consisting of 92 Viessmann Vitovolt P230RA modules and an SMA Sunny Tripower 17000TL inverter, installed at the Zwierzyniec-Bialy Słup Research and Education Centre of Roztocze National Park. The study was carried out from 1 January 2012 to 31 December 2014. The total investment cost associated with the purchase and assembly of the photovoltaic system was PLN 505 489,67. The annual value of the electric energy produced, including revenue from the sale of certificates of origin during this period, was PLN 6 793,48. The payback period for the investment was calculated at 74 years, which is more than double the anticipated exploitation period (30 years), with a present net value (NPV) of PLN 229 000. The paper also presents the results of a simulation-based calculation of the economic efficiency of such a system for three levels of investment costs: PLN 6 000 per kWp — variant 1, PLN 7 000 per kWp — variant 2, and PLN 8 000 per kWp — variant 3. The payback period ranged from 19 to 25 years, depending on the variant, and the NPV was positive for all variants.